Special Issue “An Update on Lactobacillus”: Editorial - Piotr Heczko; Łucja Kozień; Magdalena Strus (Microorganisms, 2023)
As indicated in the introduction to this Special Issue, as of 2020, the original genus Lactobacillus comprised over 260 recognized species, a figure which is probably much higher now [...]